CONTENT OF FORMATION OF MODERN PROFESSIONAL QUALITIES IN FUTURE TEACHERS OF TECHNOLOGICAL EDUCATION IN HIGHER EDUCATIONAL INSTITUTIONS (World Economics and Finance Bulletin, 2023)
As the development of the modern professional quality level of the teachers of the future technological education occurs through professional literacy and respect for national talents, it is necessary to look at the past, the traditions of the ancestors and the path they have traveled
Keywords: Modern professional quality; education; professional quality